Characteristics of Sodium Alginate/Antarctic Krill Protein Composite Fiber Based on Cellulose Nanocrystals Modification: Rheology, Hydrogen Bond, Crystallization, Strength, and Water-Resistance - Jicheng Shan; Jing Guo; Fucheng Guan; Feng Li; Chunqiu Di (Gels, 2022)
The purpose of adding cellulose nanocrystals (CNCs) into sodium alginate (SA) and Antarctic krill protein (AKP) system is to use the ionic cross-linking of SA and AKP and the dynamic hydrogen-bonding between them and CNCs to construct multiple cross-linking structures, to improve the water-resistance and strength of SA/AKP/CNCs composite fiber. Based on the structural viscosity index in rheological theory, the ratio of spinning solution and temperature were optimized by studying the structural viscosity index of the solution under different CNCs content and temperature, then the composite fiber was prepared by wet spinning. We found that when the content of CNCs is 0.8% and 1.2%, the temperature is 45 °C and 55 °C, the structural viscosity is relatively low. Under the optimal conditions, the intermolecular hydrogen bonds decrease with the increase of temperature. Some of the reduced hydrogen bonds convert into intramolecular hydrogen bonds. Some of them exist as free hydroxyl; increasing CNCs content increases intermolecular hydrogen bonds. With the increase of temperature, the crystallinity of composite fiber increases. The maximum crystallinity reaches 27%; the CNCs content increases from 0.8% to 1.2%, the breaking strength of composite fiber increases by 31%. The water resistance of composite fiber improves obviously, while the swelling rate is only 14%.